Readiness for Interprofessional Learning Among First Year Medical and Dental Students in Nepal - Jha N; Palaian S; Shankar PR; Poudyal S (Advances in Medical Education and Practice, 2022)
Nisha Jha,1 Subish Palaian,2,3 Pathiyil Ravi Shankar,4 Sijan Poudyal5 1Department of Pharmacology, KIST Medical College, Lalitpur, Bagmati, Nepal; 2Department of Clinical Sciences, College of Pharmacy and Health Sciences, Ajman University, Ajman, United Arab Emirates; 3Center of Medical and Bio-Allied Health Sciences Research, Ajman University, Ajman, United Arab Emirates; 4IMU Centre for Education, International Medical University, Kuala Lumpur, Malaysia; 5Department of Community Dentistry, KIST Medical College, Lalitpur, Bagmati, NepalCorrespondence: Nisha Jha, Department of Clinical Pharmacology and Therapeutics, KIST Medical College, Imadol, Lalitpur, Bagmati, Nepal, Tel +977 9841 602 808, Email nishajha32@gmail.com Subish Palaian, Department of Clinical Sciences, College of Pharmacy and Health Sciences, Ajman University, Ajman, United Arab Emirates, Email subishpalaian@gmail.comIntroduction: Health professional education curricula in Nepal do not include interprofessional education (IPE). Though a previous study conducted in Nepal identified positive attitudes among medical and nursing students, so far there are no studies assessing the health professional students’ readiness toward IPE. The aim of the study was to assess the readiness for IPE among medical and dental students.Methods: The present cross-sectional study explored the readiness of conveniently selected first-year medical and dental students towards IPE and compared readiness among subgroups of respondents. The readiness was assessed through an online survey using the standard Readiness for Interprofessional Learning Scale (RIPLS) during June 2021. The nineteen questions in RIPLS were categorized under four domains: teamwork and collaboration (items 1– 9), negative professional identity (items 10– 12), positive professional identity (items 13– 16), and roles and responsibilities (items 17– 19). The individual statements were scored and assessed as per the study objectives. The scores were not normally distributed, so non-parametric tests (Mann–Whitney U-test and Kruskal Wallis test) were used.Results: A total of 83 students (69 medical and 14 dental) students responded. The median total score was 75, IQR 6 with the maximum score being 95. The median (IQR) scores for the domains teamwork and collaboration were 38 (IQR 3), negative professional identity 11 (IQR 2), positive professional identity 16 (IQR 3), roles and responsibilities 10 (3). The scores were different between students aged 20 years and below = 37, and above 20 years = 38; (p =< 0.001) in the negative professional identity domain and the total score (p = 0.001). The scores were also different among those with and without previous learning exposure with other discipline students in the same class (p = 0.046). A high median score of 5 was achieved for 8 out of 19 statements in the questionnaire.Conclusion: The findings showed a high level of readiness for IPE among student respondents. Study findings can be considered as a positive factor for implementing IPE sessions.Keywords: dental, interprofessional education, medical, Nepal, undergraduate students